A comparative analysis of Islamic and postmodernist critiques of science - Hasbullah, M. (2012)
In this study, we attempt to look at the Western and Islamic critiques of science in the context of modernity. Science is one of the main drivers of modernity, and therefore, reaction to modernity is often discussed in response to modern science and Islamic science discourse. The issue of modernity covers the wider issues across various disciplines such as philosophy, history and sociology. Among the characteristics associated with modernity that have been debated by Western and Islamic scholars such as rationality, objectivity, empiricism, scientific method, the concept of progress, and secularism, and the critique of science by the Western and Islamic scholars by using argument in history and philosophy of science. In order to understand the critical interpretation, we will look at the critiques of science presented by Kuhn, Feyerabend, and the post-modernists. From the Islamic perspective, the opinion from selected Muslim thinkers, such are Nasr, Syed Muhammad Naquib, and other local Malaysian scholars such as Osman Bakar and Shaharir Mohammad Zain will be discussed to understand the picture of Islamic perspective on science, and how they perceive modern science from the critical point of view. Although both Western and Islamic tradition arise from different perspectives of intellectual traditions, but there are potentials to discuss the relationship between these two traditions especially in the aspects of similarity in the issues discussed on modernity. The comparison between two traditions will be also included differences on the issues that have been discussed from the critique of science. Through the discussion in this study, it can be seen that the discourse of science in the context of modernity in both Western and Islamic intellectual tradition are driven by the same factor, how to deal with questions and challenges associated with science and modernity. However, clear differences between the two traditions, the discourse of science from Islamic perspective associated with the Islamic ethical system, and the Islamic worldview is considered medieval and neo-platonist. On the other hand, Western intellectual tradition is influenced by the traditions of Western counter-Enlightenment thought and the Enlightenment, and re-emerged as modernist and postmodernist thought.